Law, legislation and consent in the Plantagenet Empire: Wales and Ireland, 1272-1461 - Dodd, Gwilym (Cambridge University Press, 2017)
In recent years, scholars have begun to look afresh at the dynamics of English “imperial” power in the late medieval period, but the extent to which the English dominions were subject to English law and legislation – and why and how these influences varied between the regions, and over an extended period of time – has been considered less systematically, and rarely comparatively. With its focus on Wales and Ireland this discussion explores the synergies and the strains which shaped attitudes towards the authority of the late medieval English crown and which, ultimately, determined the extent of England’s influence beyond its borders. It shows that these attitudes were often fundamentally conflicted and contradictory. It highlights the difficulties of the English crown in seeking to balance the elitist agenda of its English subjects, on the one hand, with its desire to bring the Welsh and Irish more squarely within the orbit of the English state system, on the other hand. It also highlights the often inconsistent attitudes within the dominions themselves, which veered between welcoming or resisting the interference of the English crown. The discussion emphasizes how interaction between the English crown and the people of its dominions was shaped above all by dialogue and negotiation.